2018
DOI: 10.1021/acs.jpcc.8b01898
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Mediated Morphology and Photocatalytic Activity of α-Ag2WO4 Material

Abstract: In the present work, the morphology (hexagonal rod-like vs cuboid-like) of an α-Ag 2 WO 4 solid-state material is manipulated by a simple controlled-precipitation method, with and without the presence of the anionic surfactant sodium dodecyl sulfate (SDS), respectively, over short reaction times. Characterization techniques, such as X-ray diffraction analysis, Rietveld refinement analysis, Fourier-transform (FT) infrared spectroscopy, FT Raman spectroscopy, UV−vis spectroscopy, transmission electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 49 publications
3
69
0
1
Order By: Relevance
“…e specific microstructures of the HBSMs are further elucidated by the following TEM characterizations. As observed in Figure 4 e clear contrast between the deeply dark edges and the pale center (Figure 4(a)) visually confirms the hollow feature of the HBSMs [37]. e shell of the HBSMs, which is composed of the nonclose stacking of ultrathin NSs, is estimated as ∼100 nm in thickness (Figure 4(b)).…”
Section: Structural and Physicochemical Characterizationssupporting
confidence: 61%
See 1 more Smart Citation
“…e specific microstructures of the HBSMs are further elucidated by the following TEM characterizations. As observed in Figure 4 e clear contrast between the deeply dark edges and the pale center (Figure 4(a)) visually confirms the hollow feature of the HBSMs [37]. e shell of the HBSMs, which is composed of the nonclose stacking of ultrathin NSs, is estimated as ∼100 nm in thickness (Figure 4(b)).…”
Section: Structural and Physicochemical Characterizationssupporting
confidence: 61%
“…Based on the above discussion, a plausible formation mechanism of the HBSMs can be tentatively proposed, as schematically illustrated in Figure 5. Generally, the surfactants are always used to mediate the morphology of materials [37][38][39]. After being dissolved in the mixed GC/IP solvent, the surfactant DDAB is self-assembled to form the special molecular structure in the mixed solvent through the hydrophobic-hydrophobic interaction.…”
Section: Structural and Physicochemical Characterizationsmentioning
confidence: 99%
“…It is important to emphasize that XPS is a surface technique. A plausible explanation is the presence of distinct compositions of pure and Mo-doped Ag3PO4 particles comparing their bulk and surface regions, which is typically observed in Ag-based complex oxides [46,47]. This phenomenon arises due to the terminations from distinct crystallographic planes that are exposed at the surface, which can be richer in [PO4] than bulk, lowering the overall Ag/P ratio at the surface.…”
Section: Xps Analysismentioning
confidence: 99%
“…At present, although titanium dioxide is the most widely used photocatalyst, the wide band energy, and the recombination of the photogenerated electron-hole limit its application (Asahi et al, 2001;Yan et al, 2014a;Qi et al, 2016Qi et al, , 2018. Many new semiconductor materials have then developed in recent years, such as ZnO (Qi et al, 2017), CdS (Jing and Guo, 2006;Dai et al, 2018), WO 3 (Liu et al, 2019), Ag 2 WO 4 (Macedo et al, 2018), BiVO 4 (Wang et al, 2018(Wang et al, , 2019Song et al, 2019), AgCl (Han et al, 2011), C 3 N 4 (Guo et al, 2019;Huo et al, 2019;Qi et al, 2019), etc. In 2010, Yi et al (2010) reported that Ag 3 PO 4 has noticeable absorption in the UV-visible spectral range, which can utilize visible light to oxidize water to produce oxygen and degrade organic contaminants to purify water resources.…”
Section: Introductionmentioning
confidence: 99%